Preoperative Factors Associated with Press Ganey Patient Satisfaction Scores after Anterior Cruciate Ligament Reconstruction - Perraut, Gregory T.; Zhang, Tina; Weir, Tristan B.; Schneider, Matheus B.; Aneizi, Ali; Leong, Natalie L.; Packer, Jonathan D.; Meredith, Sean J.; Henn, R Frank, III (The Journal of Knee Surgery, 2022)
Patient satisfaction is increasingly used as a metric to evaluate the quality of healthcare services and to determine hospital and physician compensation. The aim of this study was to identify preoperative factors associated with Press Ganey Ambulatory Surgery (PGAS) satisfaction scores, and to evaluate the effect of each PGAS domain score on the total PGAS score variability in patients undergoing anterior cruciate ligament reconstruction (ACLR). A review of a Press Ganey (PG) database at a single center was performed for patients undergoing ACLR between 2015 and 2019. Ninety-nine patients completed the PGAS survey and 54 also completed preoperative demographic and patient-reported outcome measures (PROMs) for an orthopaedic registry. PGAS scores were calculated and bivariate analysis was performed. Multivariable linear regression determined the effect of each of the six PGAS domains on the total PGAS score variability. In the total cohort of 99 patients, no factors were significantly associated with the total PGAS score or any domain scores. For the 54 patients who also participated in the orthopaedic registry, none of the preoperative PROMs were significantly correlated with total PGAS score. However, having a college degree (89 vs. 95 or 97 points; p = 0.02) and continuous femoral nerve catheter (92 vs. 100 points; p = 0.04) was associated with lower personal issue domain scores, while patients with a greater number of prior surgeries had worse registration domain scores (ρ = -0.27; p = 0.049). For the entire cohort, the registration and facility domains contributed the most variability to the total PGAS score, while the physician domain contributed the least. Few preoperative factors are associated with PGAS scores, and total PGAS scores do not significantly correlate with baseline PROMs. Surgeons may have limited ability to improve their PGAS scores given most of the variability in total scores stems from systemic aspects of the patient experience.
Keywords: anterior cruciate ligament reconstruction; ACL; Press Ganey; satisfaction; ACLR